The Impact of Control Pattern Difference in Mobile Applications on Developing Cognitive achievement among Students with Learning Disabilities at the Primary Level - Alsurayhi, Mazen Mohammed Mutad (Journal of Educational and Psychological Sciences, 2022)
This research aimed to identify the impact of control pattern difference in mobile applications on developing cognitive achievement among students with learning disabilities at the primary level. The research problem can be summarized in the following main question: What is the impact of control pattern difference in mobile applications on developing the cognitive achievement among students with learning disabilities at the primary level? The researcher used the quasi-experimental method to answer the main question of the research. The experiment was divided into two experimental groups: the first group was subjected to a study with the program control pattern in Mobile applications, and the second group was subjected to a study with the learner control pattern in Mobile applications. The study tool is the achievement test. The research sample consisted of (8) students with learning disabilities in the alphabets at the primary level. The results of the study found that there were statistically significant differences of 0.05 between the average results of the two experimental groups in the cognitive achievement test due to the impact the control pattern difference in mobile applications (program control pattern, learner control pattern) in favor to the program control pattern group. The researcher recommends using the mobile applications with program control pattern while providing alphabets lessons to students with learning disabilities and directing future researches on mobile applications to study the different control patterns and their relevance to ordinary students and special education students.
Keywords: mobile applications; control pattern; learning disabilities; alphabets; cognitive achievement